Investigating charm quark energy loss in medium with the nuclear modification factor of D0 -tagged jets - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (ELSEVIER, 2026)
The nuclear modification factor R-AA of charm jets, identified by the presence of a D-0 meson among the jet constituents, has been measured for the first time in Pb-Pb collisions at a centre-of-mass energy per nucleon pair root s(NN) = 5.02 TeV with the ALICE detector at the LHC. The D-0 mesons and their charge conjugates are reconstructed from the hadronic decay D-0 -> K-pi(+). Jets are reconstructed from D-0-meson candidates and charged particles using the anti-k(T) algorithm with jet resolution parameter R = 0.3, in the jet transverse momentum (p(T)) range 5
Keywords: PBPB COLLISIONS; HEAVY; SUPPRESSION; ZERO; TEV; QCD; PP; Astronomy & Astrophysics; Physics